Perancangan Aplikasi Pengelolaan Hibah Penelitian - Baskoro, B Harjo; Erdiek Ardhianto; Ghanistantiono (KALBISCIENTIA Jurnal Sains dan Teknologi, 2025)
Research and community service are part of the Tridharma of higher education that must be implemented by every lecturer. The university, in this case the Institut Bisnis dan Informatika Kosgoro 1957, provides support in the form of research and community service grants. To manage these activities, an application is needed to facilitate the management process so that it is effective and efficient. In this paper, the focus is directed at research with the assumption that both activities are essentially very similar, with only a few minor differences. The research method used is prototyping, with the result in the form of application designs in the form of flowcharts, use case diagrams, class diagrams and website design.